First trimester circulating MicroRNA biomarkers predictive of subsequentpreterm delivery and cervical shortening - Cook,J; Bennett,P; Kim,SH; Teoh,TG; Sykes,L; Kindinger,L; Garrett,A; MacIntyre,D; Terzidou,V (Scientific Reports, 2019)
Preterm birth (PTB) is the leading cause of infant death and disability worldwide. The onset of preterm uterine contractions is preceded by asymptomatic cervical remodelling and ripening, which can be seen on trans-vaginal ultrasound as cervical shortening. This study aimed to identify plasma miRNA biomarkers that predict preterm birth and/or cervical shortening. We collected serial plasma samples from pregnant women prospectively from 12 to 22 weeks gestation. The nCounter miRNA assay was used to identify differentially expressed miRNAs associated with spontaneous PTB and/or cervical shortening (n = 16 term no short, n = 13 preterm, n = 24 short). Predictive values of the miRNA biomarkers were confirmed in an independent validation cohort consisting of 96 women who delivered at term, 14 preterm and 21 early cervical shortening at <20 weeks gestation. Nine miRNAs (hsa-let-7a-5p, hsa-miR-374a-5p, hsa-miR-15b-5p, hsa-miR-19b-3p, hsa-miR-23a-3p, hsa-miR-93-5p, hsa-miR-150-5p, hsa-miR-185-5p and hsa-miR-191-5p) were differentially expressed (P < 0.001) in women subsequently experiencing PTB or cervical shortening. Hsa-miR-150-5p had the strongest ability to predict PTB (AUC = 0.8725) and cervical shortening (AUC = 0.8514). Plasma miRNAs in the first trimester can predict PTB and cervical shortening in women at risk of preterm delivery. This is a key period in pregnancy when early identification of PTB risk allows time to deliver outcome-modifying interventions.